The traveling salesman problem: algorithms, sub-tours and applications in combinatorial optimization (2020)
The importance of the traveling salesman problem (TSP) in combinatorial optimization and its application and adaptability to numerous real-life problems has led to the development of a wide range of algorithms. A major issue in the development of TSP algorithm involves how to handle the large number of subtour eliminating constraints which contribute to the exponential growth of computational time associated with TSP algorithms. In this chapter, basic concepts, development and many numerous research efforts of Professor O.E. Charles-Owaba on TSP were discussed; some of his works on the concept of the TSP set sequencing algorithm were highlighted.